2021
DOI: 10.5194/piahs-384-247-2021
|View full text |Cite
|
Sign up to set email alerts
|

Changement climatique dans le bassin versant de l'Ogooué : évolution récente et impact sur les écoulements

Abstract: Abstract. L'objectif de cet article est de faire une évaluation des tendances récentes des grandeurs hydroclimatiques dans le bassin de l'Ogooué en contexte de changement climatique. Pour cela, les données de pluies et de débits de ce bassin ont été analysées au moyen du test de Pettitt. Les résultats de cette étude révèlent une diminution statistiquement significative des modules annuels que le test de Pettitt situe en 1972–1973, mais rien de tel pour les pluies à ce même pas de temps. Les écarts des moyennes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…This is also the case in this study. However, this study reveals a reversal of these trends once known from the 2000s, which has only been demonstrated so far by very few studies [20,30].…”
Section: In the Southern Partmentioning
confidence: 45%
“…This is also the case in this study. However, this study reveals a reversal of these trends once known from the 2000s, which has only been demonstrated so far by very few studies [20,30].…”
Section: In the Southern Partmentioning
confidence: 45%
“…The lesser impact of winter precipitation on the spring ows of the Nyong between the 2000-2010 decades, has been already suggested in the literature (Ebodé et al 2020). However, it should be noted that, unlike the Nyong basin, the increase in Winter precipitation observed in the region between the decades 2000-2010 is visible in the Spring ows from basins located further south, such as the Ntem and the Ogooue (Ebodé 2020a, Ebodé et al 2021b).…”
Section: The Impact Of Precipitationmentioning
confidence: 99%
“…In equatorial Central Africa, recent studies focusing on the impact of environmental forcings on ows during the historical period have highlighted a drop in average and extreme ows linked to a drop in rainfall for some basins such as the Ntem and the Ogooue (Conway et al 2009;Ebodé et al 2020;Ebodé et al 2021b). In other basins such as the Nyong and the Mefou, it has been demonstrated that maximum ows may stay the same or increase, as a result of changes in land use patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In equatorial Central Africa, recent studies focusing on the impact of environmental forcings on flows during the historical period have highlighted a drop in average and extreme flows linked to a drop in rainfall for some basins such as the Ntem and the Ogooue (Conway et al 2009;Ebodé et al 2020;Ebodé et al 2021b). In other basins such as the Nyong and the Mefou, it has been demonstrated that maximum flows may stay the same or increase, as a result of changes in land use patterns.…”
Section: Introductionmentioning
confidence: 99%